2022
DOI: 10.21037/atm-22-5196
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV ameliorates spinal cord injury through controlling ferroptosis in H2O2-damaged PC12 cells in vitro

Abstract: Background: Spinal cord injury (SCI) is associated with significant paralysis and high fatality. Recent research has revealed that ferroptosis participates in the pathogenesis of SCI. Astragaloside IV (AS-IV), the main active ingredient of the plant Astragalus membranaceus, has been reported to promote motor function recovery in rats with SCI. This study explored the effects of AS-IV in H 2 O 2 -treated PC12 pheochromocytoma cells. Methods:The optimal concentration and duration of AS-IV treatment in PC12 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The assays for caspase-3 (Abcam, ab39401) 86 and Bax activity (Abcam, ab199080) 87 are based on cleavage of the chromogenic substrate. Control and treated cells with IC 50 of compounds 5e and 5h were harvested from 25cm 2 flasks and lysed in HCT-116 cell lysis buffer (50 nmol/l, Tris-HCL, pH 7.5, 0.03% NP40, 1.0 mmol/l DTT) for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…The assays for caspase-3 (Abcam, ab39401) 86 and Bax activity (Abcam, ab199080) 87 are based on cleavage of the chromogenic substrate. Control and treated cells with IC 50 of compounds 5e and 5h were harvested from 25cm 2 flasks and lysed in HCT-116 cell lysis buffer (50 nmol/l, Tris-HCL, pH 7.5, 0.03% NP40, 1.0 mmol/l DTT) for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…c0201S; Beyotime institute of Biotechnology) at 37˚C for 2 min. Finally, labelled cells were detected with a flow cytometer (LSRFortessa™ X-20; BD Biosciences) and analyzed by Flow v10.9 (Bd Biosciences) (37).…”
Section: Methodsmentioning
confidence: 99%
“…In a study, Astragaloside IV (AS-IV) was found to mitigate H2O2-induced damage to PC12 cells by inhibiting the generation of ROS and promoting TFEB expression, thereby preventing ferroptosis. The protective effects of AS-IV were reversed when TFEB was knocked down ( 136 ). The integrity of white matter bundles is vital for motor function recovery after SCI ( 137 ), as well as for neuronal communication and cognitive function improvement ( 138 ).…”
Section: Ros In Ferroptosismentioning
confidence: 99%